2022
DOI: 10.1038/s41467-022-32385-y
|View full text |Cite
|
Sign up to set email alerts
|

Distractibility and impulsivity neural states are distinct from selective attention and modulate the implementation of spatial attention

Abstract: In the context of visual attention, it has been classically assumed that missing the response to a target or erroneously selecting a distractor occurs as a consequence of the (miss)allocation of attention in space. In the present paper, we challenge this view and provide evidence that, in addition to encoding spatial attention, prefrontal neurons also encode a distractibility-to-impulsivity state. Using supervised dimensionality reduction techniques in prefrontal neuronal recordings in monkeys, we identify two… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 74 publications
4
17
0
Order By: Relevance
“…Finally, we found that FEF cells were tuned to the attentional focus, understood as the distance between the decoded position of the attentional spotlight to the target onset, measured before the target onset (1922). This is in line with recently reported evidence showing that attention is dynamic and rhythmic in space (22,49), and that when pooling trials based on attention to target distance, the spiking rate of FEF cells increased as closer was the attentional spotlight to the expected position of the target (21,24).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Finally, we found that FEF cells were tuned to the attentional focus, understood as the distance between the decoded position of the attentional spotlight to the target onset, measured before the target onset (1922). This is in line with recently reported evidence showing that attention is dynamic and rhythmic in space (22,49), and that when pooling trials based on attention to target distance, the spiking rate of FEF cells increased as closer was the attentional spotlight to the expected position of the target (21,24).…”
Section: Discussionsupporting
confidence: 92%
“…More specifically, the 72% of the recorded cells showed tuning to more than a single parameter. These mixed selectivity cells have been reported in different brain areas (6,37,50,51), including the FEF (21,36), and they represent a signature of the high-dimensional neural representation of relevant information and task-related parameters (7). Particularly, our results show that certain recorded cells are tuned simultaneously to more than two parameters, namely, spatial attention, the focus of attention, RTs, and CTOA.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…With appropriate pre-processing, such as dimensionality reduction or de-mixed dimensionality reduction approaches ( Kobak et al, 2016 ), SNR is enhanced, as it becomes possible to assign overall signal variance to the process of interest as well as to the cognitive processes of non-interest. Applying such dimensionality reduction approaches to MUA recordings form the FEF allows to better decode the spatial orientation of attention irrespective of whether the subjects are engaged in the task of not, thus dissociating between attention orientation and task engagement ( Amengual and Ben Hamed, 2021 ; Amengual et al, 2022 ).…”
Section: Exploring Cognitive Brain Function Using Decoding Methodsmentioning
confidence: 99%
“…For example, it has been very intriguing to us to observe that error trials could still be produced even when spatial attention was decoded close to the cued location ( Astrand et al, 2016 , 2020 ; De Sousa et al, 2021 ). De-mixed dimensionality reduction approaches ( Kobak et al, 2016 ), allowed us to demonstrate that spatial attention orientation organizes in the prefrontal cortex distinctly from engagement in the task, such that target miss-detections could arise from both an inappropriate allocation of attention or an inappropriate engagement in the task ( Amengual and Ben Hamed, 2021 ; Amengual et al, 2022 ). This biologically-inferred decoding schema further enhances our accuracy at tracking the actual spatial spotlight of attention and better account for its contribution to overt behavior.…”
Section: Exploring Cognitive Brain Function Using Decoding Methodsmentioning
confidence: 99%